KORELASI ANTARA KEMANDIRIAN DAN MOTIVASI BELAJAR TERHADAP HASIL BELAJAR TEMATIK - Dede Novianti; Sugiyono Sugiyono; Bistari Bistari (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
Abstract This study aimed to describe the correlation between independence and learning motivation on learning outcomes in the fifth grade thematic learning of SDN 46 Sungai Raya. The research method used was descriptive research with a correlational study form. The population in this study were 25 SDN 46 Sungai Raya students. The sample in this study were 25 students who were determined by the sampling technique, namely class V SDN 46 Sungai Raya totaling 26 students. The results showed that independent learning was 79.04%, learning motivation was 75.8%, and learning outcomes were obtained an average of 75.6. Statistical calculations used the product moment correlation formula, namely learning independence with learning outcomes obtained rcount of 0.78 and learning motivation with learning outcomes obtained rcount of 0.876. Independence and learning motivation on learning outcomes used the multiple correlation formula and gafe by R_ (y. 〖X_1 x〗_ (2)) of 0.775. it was categorized as a strong relationship with Fcount of 45.128 and Ftable ¬α = 5% of 3.42 which means (45,128)> Ftable ¬ (3,42), then Ha is accepted. So, it can be concluded that there was a relationship between independence and learning motivation on learning outcomes in thematic learning in class V SDN 46 Sungai Raya. Keywords Correlation,Independent Learning, Learning Motivation, Learning outcomes